Spray-dried doxorubicin-albumin microparticulate systems for treatment of multidrug resistant melanomas Read More: http://informahealthcare.com/doi/abs/10.3109/1061186X.2010.504270 - Alphia, K.J.; Bejugam, N.K.; Nettey, H.; Addo, R.; D’Souza, M.J. (Journal of Drug Targeting, 2011)
As multidrug resistance continues to be a problem in cancer treatment, controlled release delivery systems, such as microspheres, may aid to give a slower release of anticancer drugs into drug resistant tumor cells. In this study doxorubicin microspheres microencapsulated in an albumin matrix were prepared via the spray-drying method and characterized for particle size, content analysis, and release studies. They were then evaluated in vitro using drug resistant murine melanoma tumor cells for uptake and efflux studies. Spray-drying produced a dispersed powder with a mean particle size of 4.91 ± 1.2 µm, 60% product yield, and encapsulation efficiency of 85% and a ζ potential range of 37 to −40 mV. Intracellular doxorubicin concentrations were higher in drug resistant tumor cells treated with microspheres as opposed to solution, and efflux of doxorubicin from the tumor cell was inhibited. Greater cytotoxic effects were seen in tumor cells treated with doxorubicin microspheres versus solution up to and after 3 days. In vivo pharmacokinetic studies conducted in male Sprague–Dawley rats, revealed a plasma-level time curve indicative of a two-compartment model, and showed prolonged half-life of doxorubicin, greater area under the plasma concentration time curve, and increased plasma concentrations of doxorubicin in rats at 8 and 24 h after administration of doxorubicin microspheres. Read More: http://informahealthcare.com/doi/abs/10.3109/1061186X.2010.504270
Keywords: Microspheres, doxorubicin, multidrug resistance, spray-drying, melanoma tumor cells. Read More: http://informahealthcare.com/doi/abs/10.3109/1061186X.2010.504270